Production costs structure as a determinant of the deflator of household consumption: The Input-Output approach - Artur Gorzałczyński (Economic and Environmental Studies (E&ES), 2019)
The presented considerations are an attempt to verify the possibility of using input-output tables for modeling and, as a consequence, to forecast inflation. The study is a continuation of previous simulation experiments performed on a limited statistical material. The study uses input-output tables expressed in current and constant prices, describing the economy of Denmark. This is the richest available set of tables of this type. Thanks to these tables it was possible to trace long-term changes in the structure of production costs and their impact on the deflator of household consumption.
Keywords: C67; C43; E31; 330; input - output model; inflation; cost structure of production